Linnik's large sieve and the L1$L^{1}$ norm of exponential sums. Issue 2 (2nd December 2022) - Eckels, Emily; Jin, Steven; Ledoan, Andrew; Tobin, Brian
Abstract: The elementary method of Balog and Ruzsa and the large sieve of Linnik are utilized to investigate the behaviour of the L 1 $L^{1}$ norm of an exponential sum over the primes. A new proof of a lower bound due to Vaughan for the L 1 $L^{1}$ norm of an exponential sum formed with the von Mangoldt function is furnished.